PRINSIP BISNIS DALAM PERSPEKTIF HUKUM EKONOMI ISLAM - Azazy, Yusup; Rusmani, Rusmani (Al-Muamalat: Jurnal Ekonomi Syariah, 2018)
ABSTRACTHuman life can not be separated from the need when the need to dominate the economic role is crucial in meeting the needs. One of the economic activities to meet the needs of human life is to do business. Not a few people when running a business that is mired in the abyss prohibition, doubtful even collapse. Therefore, the Qur'an (Islamic Economic Law) offers some of the business concept is the concept of an-taradhin, do not do business since Friday call to prayer echoed through the Friday prayers finished, anti-usury, anti-hoarding, self-owned goods , does not contain elements gharar, do not contain elements of deception, ridak buying and selling hashat (lottery), not buying and selling mulamasah (by touching) and goods yangdijual unclean. So that businesses in Islam would appear the characteristics of not only benefit the material alone, but the essential advantage that ukhrawi. Basic business law in Islam is the Qur'an, al-Hadith and Shariah Economic Law Compilation. The benefits when doing business in accordance with Islamic rules will bring benefits worth blessing. In addition, stakeholders associated with this business will not be harmed harmed.